INDANYL ANALOGS AS POTENTIAL ANTIMICROBIAL AGENTS - Mandal, Sudip Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The wide variety of biological activities of different indane derivatives makes them an interesting moiety in the field of medicinal chemistry. The objective of the study was to identify and develop novel antimicrobial agents from indanyl analogs. Methods: Recently synthesized indanyl analogs (4a-c and 5a-o) were examined against various pathogenic microorganisms (Gram-positive and Gram-negative bacteria and fungi) using serial dilution method. These analogs were found to possess antibacterial and antifungal activities with minimum inhibitory concentration values ranging between 1.56 and 100 Î¼g/mL. Results: The results revealed that the entire compounds showed mild-to-moderate antibacterial activities and moderate-to-excellent antifungal activities against the pathogenic microorganisms as compared to the standard drugs ciprofloxacin and fluconazole, respectively. Compounds 4a, 5a, 5b, 5d, 5e, 5i, and 5j exhibited antifungal activities superior to the reference drug. Conclusion: Based on the structure-activity relationship, it can conclude that the indan-3-oxo-1-acetic acid moiety is essential for the activities and lipophilic alkoxy substituents on indane ring have enhanced the biological activity. Further, structure-activity relationship studies of the compounds 4a, 5a, and 5b are needful to find the new lead as antimicrobial agent.